Do cultivar, geographical location and crop season influence phenolic profile of walnut leaves? - Amaral, Joana S. (2008)
Walnut leaves from nine different cultivars (Arco, Franquette, Hartley, Lara, Marbot, Mayette, Meylannaise, Parisienne and Rego) were studied for their phenolic compounds. Samples were harvested along three consecutive years, at two different geographical locations, in order to evaluate if significant differences in the phenolics composition can be related with genetic, climatic or geographical factors. Nine compounds (3-caffeoylquinic, 3-p-coumaroylquinic and 4-p-coumaroylquinic acids, quercetin 3- galactoside, quercetin 3-arabinoside, quercetin 3-xyloside, quercetin 3-rhamnoside, a quercetin 3-pentoside derivative and a kaempferol 3-pentoside derivative) were quantified using an HPLC-DAD methodology. The qualitative profiles were identical for all samples, but differences were observed in terms of individual compounds’ contents. Multivariate statistical analysis was carried out, showing that significant differences exist among production years, which can be related to climatic reasons.